Enhancing Hygiene and Technical Properties of Ceramic Tiles through Moroccan Phosphate Additives - Boutaleb, Fatima Zahra; Boutaleb, Nadia; Bahlaouan, Bouchaib; Hadidi, Meryem; Benjelloun, Ghita Radi; Louanjli, Fatima Azzahra; Doublali, Fatima Ezzahra; El Antri, Said (European Scientific Journal, ESJ, 2024)
This study offers a simple solution to manufacture ceramic tiles with good technical and hygienic properties. This solution consists of integrating the phosphate product from Morocco in the industrial formulation of ceramic tiles, to produce materials in compliance with the criterion of the ISO standard. For phosphate products, three grades were studied: HG-high grade, MG-medium grade, and LG-low grade. The results show that for materials containing these additives, there is both an effect of the concentration and type of additive on technical and hygienic properties. The mechanical property is improved when the incorporated component was richer in P2O5. Only the use of HG-high grade and MG-medium grade as an additive at least 15% makes it possible to satisfy the mechanical requirement. The anti-biofilm effect of natural phosphate (PN) as an additive to manufacture ceramic tiles is confirmed, it may prevent bio adhesion and biofilm formation at almost 75% for the HG-high grade and MG-medium grade. This solution could interest professionals and all users who care about the state of hygiene of their ceramic materials sensible to the formation of biofilm, like orthopaedic implants, swimming pool tile…etc.